2021
DOI: 10.1126/sciadv.abj6928
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic evidence for a disk substructure in the early solar system

Abstract: Astronomical observations and isotopic measurements of meteorites suggest that substructures are common in protoplanetary disks and may even have existed in the solar nebula. Here, we conduct paleomagnetic measurements of chondrules in CO carbonaceous chondrites to investigate the existence and nature of these disk substructures. We show that the paleomagnetism of chondrules in CO carbonaceous chondrites indicates the presence of a 101 ± 48 T field in the solar nebula in the outer solar system (~3 to 7 AU fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 63 publications
10
58
0
Order By: Relevance
“…Fig. 7 shows the results of the CO chondrites in context with those of previous studies (Biersteker et al, 2019;Borlina et al, 2021;Bryson et al, 2017Bryson et al, , 2020Cournede et al, 2015;Fu et al, 2014Fu et al, , 2020Fu et al, , 2021Gattacceca et al, 2016;Wang et al, 2017;Weiss et al, 2017). We present in Fig.…”
Section: Solar Nebular Magnetic Fields and Implications For The Dissi...supporting
confidence: 58%
See 3 more Smart Citations
“…Fig. 7 shows the results of the CO chondrites in context with those of previous studies (Biersteker et al, 2019;Borlina et al, 2021;Bryson et al, 2017Bryson et al, , 2020Cournede et al, 2015;Fu et al, 2014Fu et al, , 2020Fu et al, , 2021Gattacceca et al, 2016;Wang et al, 2017;Weiss et al, 2017). We present in Fig.…”
Section: Solar Nebular Magnetic Fields and Implications For The Dissi...supporting
confidence: 58%
“…(B) Points show paleomagnetic constraints from (A) as a function of age (see text for details on the estimates of the ages). tween 10 −8 and 10 −7 M year −1 and provide lower limits to the accretion rate when compared to that reported by Borlina et al (2021) from dusty olivine chondrules in CO chondrites. Comparing the accretion rate inferred from the lower limit of the paleointensity from the LL chondrules (Fu et al, 2014) to the models shown in Fig.…”
Section: Predicted Midplane Fieldmentioning
confidence: 49%
See 2 more Smart Citations
“… 2021 ; Borlina et al. 2021 ). Recent magnetohydrodynamic simulations indicate this field could have been temporally steady for (Weiss et al.…”
Section: How We Will Use Our Data To Determine Psyche’s Originmentioning
confidence: 99%